Travel distance may have a negative impact on the outcome of deep brain stimulation in Parkinson’s disease - Hemeda Sahar; Dávid Pintér; Evelyn Pintér; István Balás; József Janszky; Norbert Kovács (Scientific Reports)
Abstract Potential beneficial effects of teleprogramming on the efficacy of deep brain stimulation (DBS) have not been studied. We aimed to explore the effects of travel distance on the outcome of DBS in Parkinson’s disease (PD). We retrospectively analyzed travel- and visit-related data of PD patients treated with DBS. Comparing the first-year and five-year outcomes of far-living patients (> 50 km) having the desired number of follow-up visits (n = 74) to those of far-living subjects having less visits than optimal (n = 54), patients with desired number of visits had better global health-related quality of life according to summary indexes of disease-specific and non-specific scales at five years. Far-living patients with desired number of visits had larger decrease in Parts II, III and IV of the Movement Disorder Society-sponsored Unified Parkinson’s Disease Rating Scale from baseline to the five-year follow-up and more simplified antiparkinsonian medication treatment. Even 40% of PD patients with DBS who live far from the movement disorder center may have less in-person visits than optimal and be on the risk of having worse long-term outcome of DBS than could be achieved. Teleprogramming may help maintaining the long-term efficacy of stimulation in this group of patients.